2011
DOI: 10.5539/jas.v3n4p241
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Rabbits Fed Diets Containing Different Levels of Energy and Lesser Galangal (Alpinia Officinarum)

Abstract: This work aimed to study the effect of two different levels of ration energy supplemented with Alpinia officinarum. Rabbits were classified into six equal groups (G1-G6). The 1 st and 4 th groups received basal ration with 100 % and 90 % energy requirement and served as first and second control respectively. The 2 nd and the 3 rd groups received basal ration with 100 % energy requirement supplemented with Alpinia officinarum at the level of 0.5 and 1.0 %, respectively. The 5 th and 6 th groups received basal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Also, Srividya et al (2010) suggested that this positive effect on the performance traits of laying chickens due to galangal supplementation may be because it improves intestinal enzymes (glucase, oxidase, catalase, and peroxidase) that may be associated with better digestibility of different nutrients. Ibrahim et al (2011) reported that galangal has strong antioxidants and stimulates the body's immunity process; this may increase the growth performance and health status of laying hens that are reared under heat stress conditions. Blood constituents Data from Table (3) shows the chick's blood analysis, where it is noted that when compared to the control group, serum glucose levels were increased significantly (P=0.001) with galangal treatments, reaching 115.5, 117.4, 118.7, and 118.1 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Srividya et al (2010) suggested that this positive effect on the performance traits of laying chickens due to galangal supplementation may be because it improves intestinal enzymes (glucase, oxidase, catalase, and peroxidase) that may be associated with better digestibility of different nutrients. Ibrahim et al (2011) reported that galangal has strong antioxidants and stimulates the body's immunity process; this may increase the growth performance and health status of laying hens that are reared under heat stress conditions. Blood constituents Data from Table (3) shows the chick's blood analysis, where it is noted that when compared to the control group, serum glucose levels were increased significantly (P=0.001) with galangal treatments, reaching 115.5, 117.4, 118.7, and 118.1 %, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant action of galangal, according to Zhao et al (2010), is attributable to the presence of polyphenols, anthocyanin, glycosides, and thiocarbamates, which scavenge free radicals. Galangal also has a strong antioxidant capacity due to a combination of polyphenolic components (Ibrahim et al, 2011;Das & Santhy, 2015;Pahwa et al, 2016 andAbdel-Azeem andBasyony, 2019). The objective of this investigation was to study the impacts of galangal supplementary in broiler diet on productive performance, blood biochemical parameters, antioxidant status, carcass traits, economic efficiency and production index.…”
Section: Introductionmentioning
confidence: 99%